Bugweed biocontrol: new insights into the biological control agents of Solanum mauritianum, Gargaphia decoris and Anthonomus santacruzi - Cowie, Blair William (My University, 2016)
Solanum mauritianum Scopoli (Solanaceae) is a perennial tree or shrub native to South America, which has become a prominent and widespread invader in numerous sub-tropical countries around the world. In South Africa, S. mauritianum is listed as one of the country’s worst ecological weeds, having been targeted for biological control efforts since 1984. Despite some constraints, biocontrol efforts have seen the successful release of two promising biocontrol agents. The first of these biocontrol agents, released against S. mauritianum, was the sap-sucking lace bug, Gargaphia decoris Drake (Hemiptera: Tingidae). Sap-feeding by G. decoris metabolically impaired the leaves, resulting in a reduction to their photosynthesis, with a greater effect on plants growing in full-sun compared to plants growing in the shade. This difference was attributed to higher leaf temperatures experienced in the sun. Herbivory reduced transpiration rates by more than 50%, resulting in a reduction in evaporative cooling of the leaf. The increased physiological damage experienced by full-sun plants may be a combination of stresses, particularly the direct effect of chlorophyll removal via herbivory and the indirect effect of accumulated heat–light stress. The flowerbud-feeding weevil, Anthonomus santacruzi Hustache (Coleoptera: Curculionidae), was released in 2008 as a biological control agent against S. mauritianum. The hypothesis that climate, particularly low temperature and low relative humidity, restricts the survival and establishment of A. santacruzi in South Africa was tested. Thermal assessments on A. santacruzi adults calculated the CTmin and LT50 as 4.1 ± 0.2 °C (n = 20) and 4.2 ± 0.3 °C (n = 90) respectively. The LH50 of A. santacruzi adults was calculated as 46.9%. The establishment of A. santacruzi at only the warm and humid release sites in South Africa advocates for the consideration of low temperature and low humidity as factors impeding the agents’ establishment and spread, particularly on the cooler and drier Highveld. Furthermore, the impact of A. santacruzi’s florivory on the reproductive output of S. mauritianum, as well as the potential of the agent to act as an indirect pollinator was assessed. Overall direct floral damage caused by A. santacruzi was trivial, with only ~5% of the anther and ~2% of the petal area being removed. However, the consequent effects of A. santacruzi were considerably more damaging, with 25% and 66% reductions in flowering and fruiting respectively. Additionally, fruits produced from inflorescences exposed to A. santacruzi were smaller in size, with fewer, less viable seeds. The feeding and presence of A. santacruzi also maintains the potential for indirect effects on the pollination of S. mauritianum. This suggests that in areas with well-established A. santacruzi populations, the weevils may simultaneously facilitate the self-pollination and potential inbreeding of S. mauritianum. Keywords: Agent impacts and effects; biological control; Bugweed; climatic unsuitability; ecophysiology; indirect effects; post-release evaluation.
A Dissertation submitted to the Faculty of Science, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science, Johannesburg, South Africa. 2016.
Keywords: Biological pest control agents; Weeds--South Africa